Immobilized enzyme with sustainable chestnut biochar to remediate polycyclic aromatic hydrocarbons contaminated soils - Zhao, Huan (Environmental technology, 2024)
Polycyclic aromatic hydrocarbons (PAHs) contaminated soil severely and are difficult to remediate. In this study, acid-modified chestnut inner shell biochar with abundant pore channels was used as the main raw materials for the immobilization of white-rot fungal crude enzyme. The maximum immobilization rate of crude enzymes (97.25%±6.20%) could be achieved under the optimal conditions of 24 h immobilization of 10 U/mL crude enzymes by 1 g biochar at 25℃ and pH = 5. Meanwhile, immobilization improved the stability of the crude enzyme. The relative activity of the immobilized crude enzyme increased by 59.32% and 49.73% (compared to the free crude enzymes) after 5 weeks of storage at 4°C and 25°C, respectively. It has been verified that chestnut-based immobilized crude enzyme can degrade 37% of benzo[a]pyrene in 10 days for PAHs-contaminated soils. An efficient, feasible, and low-cost remediation method for PAHs-contaminated soils was explored, which provides technical support for the application of crude enzymes in organic contaminated soils